Jejunal Rupture Associated with a Traumatic Partial Pubic Symphysial Separation in a Dog - Marti, J. M.; Wells, K. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
A distal jejunal perforation was caused by entrapment in a minimally displaced pubic symphysial separation and ischial fracture caused by a road accident. Other pelvic fractures were not identified.Faecal material leaked into the retroperitoneal space of the pelvic cavity and produced a pararectal enterocutaneous fistula one week after the accident. Obvious evidence of septic peritonitis was not present, although a uro-abdomen was identified as a result of an avulsed ureter. Nephro-ureterectomy, intestinal resection and anastomosis and fracture repair procedures were carried out but the patient was euthanatised two days postoperatively.Small intestinal injury associated with pelvic trauma is extremely uncommon in the dog. In previously reported cases, intestinal loops were damaged by comminuted pubic fractures or the callus reaction during their healing process. In the Case Reported here, a jejunal loop was trapped in a partial pubic symphysial separation caused by an automobile accident.
Keywords: Pelvic trauma; intestinal rupture; enterocutaneous fístula